2022
DOI: 10.1007/s00592-022-01878-z
|View full text |Cite
|
Sign up to set email alerts
|

Significant and persistent improvements in time in range and positive emotions in children and adolescents with type 1 diabetes using a closed-loop control system after attending a virtual educational camp

Abstract: Objective To evaluate the six-month impact of the advanced automated functions of a closed-loop control (CLC) system (Control-IQ) and a virtual educational camp (vEC) on emotions and time in range (TIR) of children and adolescents with type 1 diabetes. Methods Children and their parents participated in a three-day vEC. Clinical, glucose, and emotion data were evaluated before, just after, and six months after the vEC. Emotions were evaluated using adapted Plutchik's and Geneva Emotion Wheels. Results Forty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…On the other hand, we have previously reported a better improvement in TIR in Italian patients treated with a different HCL system (+11% after 6 months). 10 Similarly to previous papers reporting a decline in auto-mode use over time, 5,11,12 overall, the children and adolescents in our study presented a decrease in glucose calibrations and daily fingersticks, and thus in CGM and HCL use, confirming that the burden of technology may lead to underutilization of the system functionalities. As higher automode use and lower HbA1c level are correlated, 5,12 we suggest that the progressive underutilization of system functionality accounts for lack of improvement in HbA1c at 24 months.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, we have previously reported a better improvement in TIR in Italian patients treated with a different HCL system (+11% after 6 months). 10 Similarly to previous papers reporting a decline in auto-mode use over time, 5,11,12 overall, the children and adolescents in our study presented a decrease in glucose calibrations and daily fingersticks, and thus in CGM and HCL use, confirming that the burden of technology may lead to underutilization of the system functionalities. As higher automode use and lower HbA1c level are correlated, 5,12 we suggest that the progressive underutilization of system functionality accounts for lack of improvement in HbA1c at 24 months.…”
Section: Discussionsupporting
confidence: 87%
“…1 Time in range significantly increased after 1 week of using the upgraded closedloop system, and this improvement was maintained over time. 5,6 This study does, however, have some limitations. It is not possible to separate out the individual associations of education and technology with the TIR, although both factors are likely to be associated with the TIR.…”
Section: Discussionmentioning
confidence: 95%
“…In 2020, when an upgraded closed-loop system was introduced in Italy, a virtual educational camp (vEC) was organized for children and adolescents with type 1 diabetes. 5 , 6 Nineteen Italian pediatric diabetes centers participated in this IRB-approved, prospective, multicenter clinical cohort study, which was approved by the Azienda Socio-Sanitaria Territoriale Cremona institutional review board. Patients’ parents provided written consent for participation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several multicenter randomized trials and real-life studies in children, adolescents, and adults demonstrated the efficacy of the Control-IQ technology when compared to the sensor-augmented pump, Basal-IQ technology, and other AHCL systems (14)(15)(16)(17)(18)(19)(20). The Control-IQ technology has been shown to be effective in terms of patient satisfaction, improvement of quality of life and quality of sleep for patients and parents, ease of use, and improvement of positive emotions (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%